Pursuing gender-transformative change in customary tenure systems: civil society work in Zambia. Issue 7 (3rd October 2018) - Caron, Cynthia M.
ABSTRACT: This article examines activities undertaken by civil society organisations in Zambia to create gender-transformative change in customary tenure systems. It is based on primary data collected through interviews and group discussions with NGO representatives, lawyers and women's rights advocates, chiefs, women leaders, and local community members. The findings show that organisations pursue change by leveraging global and national frameworks and discourses and working with traditional authorities, local magistrates, men and women at the village level. Promoting gender transformative change requires multi-level networking and working across hierarchies of power that extend from the household to the state.